Reação de acessos e cultivares de meloeiro a Pseudoperonospora cubensis e identificação de Quantitative Trait Loci de resistência do meloeiro ao míldio - Albuquerque, Leidiane Bezerra (Universidade Federal Rural do Semi-Árido, 2014)
Downy mildew, caused by the fungus Pseudoperonospora cubensis, is a major threat to the production of melons in wetlands worldwide. Despite its importance, there are few studies involving the assessment of sources of resistance, as well as the identification of molecular markers that are connected to this feature and that may help breeders in marker-assisted selection (MAS). Given this, the objectives of this work were promote the selection of sources of resistance to downy mildew, from melon accessions, collected from different states in the Northeast region of Brazil and to identify QTLs that co-segregate with the resistance gene of this pathogen, using the F2:3 obtained from parents and Védrantais MR-1, contrasting to the register character. To identify sources of resistance, thirty-six accesses and four commercial cultivars in a randomized block design (RBD) were assessed with three replications and seven plants per plot, which evaluation was made on the field. The evaluation was carried out on 24 days after transplanting the seedlings to the field, when 50% of plants reached the stage of flowering, with the aid of a diagrammatic scale. It was observed that there is variability in melon germplasm for reaction to downy mildew. The accessions A1, A4, A6, A9, A12, A17, A18, A23, A27, A35 and A36 were considered promising for use in breeding programs aiming resistance to P cubensis. All commercial cultivars analyzed were highly susceptible to the pathogen. To identify markers connected the resistance QTLs, MR-1 and Védrantais parents were crossed and subsequently the F2 generation was obtained. It was extracted the DNA for evaluation molecular of the 98 plants obtained with microsatellite primers polymorphic selected from contrasting parents. Of F2 plants were obtained 98 progenies F2:3 that were used for the assessments phenotypic of the severity caused by P. cubensis, it was used the same time assessment described in the previous experiment, the period April-June 2013. The experimental design utilized was lattice simple 10 x 10. The efficiency of lattice was low (100.28%) thus data were analyzed in DBC. Significant genetic differences (P<0.01) between the progenies were identified. The estimated of heritability was considered high (86.75%), indicating successful selection. Were found 23 primers polymorphic, of this sum, thirteen amplified in all the population and were used for analyzes genotypic. Of these, ten markers presented values below level critical specified by FDR test. There was more proportion allele of parent Védrantais for eight loci, while there was more proportion allele the parent MR-1 for two loci. For other loci (three), frequencies allelic did not change. The values coefficients of determination (R2) obtained for the markers were relatively low in population. By regression simple linear, the markers explained the feature in population F2:3 the most were CMBR 139 and CMMS 22-2, being the same identified by regression multiple linear, thus they can also be used in SAM
Reaction of cultivars and accessions of melon Pseudoperonospora cubensis and the identification of Quantitative Trait Loci for resistance to downy mildew of melon
Keywords: Cucumis melo L.; Germplasm; DNA markers; Resistance gene; Cucumis melo L.; Germoplasma; Marcadores de DNA; Resistência genética; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA